PENGARUH PANDANGAN HIDUP MASYARAKAT JAWA PADA ARSITEKTUR RUMAH JOGLO - Wita & Arie Widyandini & Purnomo (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2009)
AbstractThe people of Java have a life contemplation, and they use it as a life-conduct or a life-guide when they accomplish their life.  The people of Java to be conscious that their self are a part of nature, and they very depend on it too.  That’s the reason why the people of Java try to make their life harmonious with nature.Another characteristic the people of Java is devineness.  Formerly, they believe with animism and dinamism, but they believe in religion at least. It happens after Hindu, Budha, and Islam come to Java.  Animism and Dinamism slow disappears from Java, but in several place in Java like Yogyakarta and Surakarta, animism and dinamism still exist as a tradition.The life contemplation have a big influence to people of Java, especially when they would build their traditional house, Joglo.  In Joglo, we can find lots of symbols which represent the people of Java’s intention or desire.Key words : life contemplation, Java, Joglo.